Isolation and Identification of IAA-Producing and Phosphate-Solubilizing Rhizobacteria from Sesuvium portulacastrum and In Vitro Growth-Promotion Effect on Vigna radiata L. - Yuliana, Baiq Fadilla; Zulkifli, Lalu; Rasmi, Dewa Ayu Citra; Sedijani, Prapti (Jurnal Biologi Tropis, 2025)
Sesuvium portulacastrum is a coastal plant resistant to high salt content and drought. Exploration of rhizosphere bacteria is necessary to obtain potential isolates that can be developed as biofertilizers in the future. This study aims to isolate and identify rhizosphere bacteria from Sesuvium portulacastrum that are able to produce Indole Acetic Acid (IAA) and dissolve phosphate, and to test their effects in vitro on the germination of Vigna radiata L. Rhizosphere bacteria from the Bagek Kembar Mangrove Ecosystem Area, Sekotong, West Lombok Regency. A total of 14 bacterial isolates were successfully obtained and characterized based on morphological, physiological, and biochemical properties. All isolates produced IAA qualitatively and quantitatively (19.85–33.71 ppm) with isolate KT1 having the highest production (33.71 ppm). Qualitative phosphate solubilization test showed that 12 isolates were able to form a clear zone, while quantitatively it ranged from 7.86 to 16.18 ppm with isolate K8 having the highest value (16.18 ppm). Selected isolates KT1 (the highest IAA producer), K8 (the highest phosphate solubilizer), and K5 (both with high abilities) were tested for their effect on mung bean germination. Inoculation had a significant effect on plant height, root length, and dry weight (p<0.05). These results indicate that S. portulacastrum rhizosphere bacteria have the potential to be an environmentally friendly biofertilizer for plants in high-salinity soils.